2008
DOI: 10.1111/j.1442-200x.2008.02571.x
|View full text |Cite
|
Sign up to set email alerts
|

Secondary osteoporosis in long‐term bedridden patients with cerebral palsy

Abstract: Risedronate therapy is effective for patients presenting with secondary osteoporosis with cerebral palsy. Moreover, it is desirable to treat patients more aggressively from the early stage because risedronate is not affected by the patients' other factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…The majority of subjects showed increased BMD or reduced bone pain [21,38,39,40,41,42,43,44,45,46,47,48]; a reduced fracture rate was reported in patients with quadriplegic cerebral palsy [48]. …”
Section: Bisphosphonate Use In Pediatric Patientsmentioning
confidence: 99%
“…The majority of subjects showed increased BMD or reduced bone pain [21,38,39,40,41,42,43,44,45,46,47,48]; a reduced fracture rate was reported in patients with quadriplegic cerebral palsy [48]. …”
Section: Bisphosphonate Use In Pediatric Patientsmentioning
confidence: 99%
“…It has recently been reported that these patients often sustain fractures without a clear causal event [15][16][17][18][19] . Therefore, BMD testing is often used to evaluate the extent of bone loss in CP patients with secondary osteoporosis 15,17 . It is also used to assess bone loss in Turner syndrome 20 , Pompe disease 21 , and other endocrinopathic disease 22 .…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, the authors compared sodium valproate 13,14,23 and carbamazepine 12,23 , which would influence bone metabolism, with zonisamide and clobazam 14 . It was subsequently reported that there were no statistically significant differences among the type of AED, the number of drugs used in combination, or changes in BMD 15 . In the present study, the same results were recognized and it is believed that therapy with AEDs for 3 years is beneficial for cases of secondary osteoporosis in severely handicapped children with CP (Table 1).…”
Section: Effects Of Aeds On Secondary Osteoporosismentioning
confidence: 99%
See 1 more Smart Citation
“…Hypogonadism, inadequate nutrition (including calcium and vitamin D deficiency), excess thyroxine or GC replacement, malabsorption, and impaired mobility should also be addressed as part of the overall management plan. Whilst administration of vitamin D and calcium can improve BMD in children with CP and who were treated with AEDs compared to untreated patients [75,76], there is no clear evidence that the use of vitamin D supplements in vitamin D-sufficient children with chronic disease prevents or treats secondary osteoporosis.…”
Section: General Approachmentioning
confidence: 99%